The incidence of adult obesity is associated with parental and adolescent histories of obesity in North Sumatra, Indonesia: a cross-sectional study - Sari, Dina Keumala; Ichwan, M; Masyithah, Dewi; Dharmajaya, Ridha; Khatib, Alfi (Dove Medical Press, 2021)
Purpose: Obesity that occurs in adulthood is influenced by various factors, not only energy balance, especially concerning the amount of energy consumed, but also heredity. The hereditary factors of obese parents on childhood obesity have been studied, but what about adulthood? This study examines the relationship between a history of obesity in adolescence, and maternal and paternal incidences of adult obesity. Patients and Methods: This study was a cross-sectional study that included adult men and women aged 20–60 years old. The subjects had no chronic or metabolic disease. This research was conducted from April to November, 2020, in North Sumatra Province, Indonesia. The parameters studied were demographics, daily food intake, anthropometry and a history of obesity in adolescence, and for the participants’ fathers and mothers. The statistical test used was the chi-squared test/Fisher test. Results: This study included 136 research subjects, 60 male and 76 female; based on the results of the study, 47.8% were found to be obese, but food intake showed a low intake (96.2%). There was a significant relationship between a history of obesity in adolescence and incidences of obesity (≥30 kg/m2 ) in the mother and father, with significance values of p=0.01, p=0.004, and p=0.001, respectively. Conclusion: This study found that there was a significant relationship between a history of obesity in adolescence and incidences of adult obesity (≥ 30kg/m2) in parents, but not with the level of food intake per day. The risk of obesity will increase further with a history of obesity in parents and obesity in adolescence, and this can be used to understand and prevent obesity